Farmers' Adaptation to Modern Agricultural Production Pattern Dynamics in Surumana Village, Donggala Regency - Suardin Abd. Rasyid; Suasa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
Modernization, rationalization, and commercialization of the agricultural and rural sectors are impossible to resist when communities open up owing to the impact of contemporary culture. Unlike in Java, where the majority agricultural modernisation occurred in the rice field sector, modernization occurred in both the rice field and the plantation sectors in the communities surveyed. The purpose of this research is to identify farmers' response to the dynamics of changes in agricultural production patterns, as well as the growth of modernization, rationalization, and commercialization in Surumana Village. The observed events are described using a qualitative method in this work. This study's data set includes both secondary and primary sources. Secondary data was gathered through searching relevant library resources and needed papers, while primary data was gathered by observing and conducting in-depth interviews. To collect primary data in the field, a total of 11 informants were purposefully chosen to be questioned in depth based on the study topic. The findings indicate that the agricultural production pattern in the research village has shifted toward commercialization and rationalization attempts to achieve economic rewards. Previously, the manufacturing pattern was primarily meant to fulfill the demands of basic minimalists. As a result, the shift in management patterns and farmers' production techniques toward a more logical and modern direction is a kind of farmer adaptation to the rise of modernization, rationalization, and commercialization in the village's agricultural sector.